2018
DOI: 10.2169/internalmedicine.9537-17
|View full text |Cite
|
Sign up to set email alerts
|

Pleurisy Caused by <i>Mycobacterium abscessus</i> in a Young Patient with Dermatomyositis: A Case Report and Brief Review of the Literature

Abstract: M. abscessus is a rapidly growing mycobacteria (RGM) and is the most common cause of pulmonary RGM infection. M. abscessus pleurisy is extremely rare. We herein report the case of a young patient with M. abscessus pleurisy without any lung lesions. A laboratory analysis of the pleural effusion revealed lymphocyte predominance and increased adenosine deaminase, similar to the findings observed in tuberculous pleurisy. The patient was initially treated for tuberculous pleurisy, which resulted in the partial impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The prevalence of NTM disease in China has increased in the past few decades just like in other sites of the world(14). Recently , several reports describing PE in patients with NTM disease have been published(10,(15)(16)(17)(18)  Compared with other studies, we summarized three important clinical observations: 1) Almost every patient with NTM pleurisy had a delay in diagnosis; 2) A high proportion of patients had an low CD4-positive T-cell counts, autoimmune disorders and corticosteroid therapy; 3) Most patients, especially MAC-related pleurisy, developed pyopneumothorax with BPF.…”
mentioning
confidence: 93%
“…The prevalence of NTM disease in China has increased in the past few decades just like in other sites of the world(14). Recently , several reports describing PE in patients with NTM disease have been published(10,(15)(16)(17)(18)  Compared with other studies, we summarized three important clinical observations: 1) Almost every patient with NTM pleurisy had a delay in diagnosis; 2) A high proportion of patients had an low CD4-positive T-cell counts, autoimmune disorders and corticosteroid therapy; 3) Most patients, especially MAC-related pleurisy, developed pyopneumothorax with BPF.…”
mentioning
confidence: 93%
“…Moreover, he did not have any radiological findings of a pulmonary NTM disease, and M. xenopi was not isolated from his sputum. The only other reported case in the literature of M. xenopi pleuritis had concurrent pulmonary infection [18], and we found only a few cases of NTM pleuritis of any species with no obvious pulmonary involvement [27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 60%
“…The only other reported case in the literature of M. xenopi pleuritis had concurrent pulmonary infection [18], and we found only a few cases of NTM pleuritis of any species with no obvious pulmonary involvement [27–33].…”
Section: Discussionmentioning
confidence: 99%
“…But we should treat cautiously samples that are isolated from respiratory tract specimens such as sputum and bronchoalveolar lavage fluid. Shu et al reported that the prognosis of NTM pleurisy patients with single and multiple positive results were not markedly different [ 4 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the characteristics of pleural effusion are important threads. In previous reports, the characteristics of NTM-associated pleurisy are unknown in comparison to tuberculous pleurisy and the predominant cell types of pleural effusion were different [ 18 , 19 ]. Most cases revealed a high leukocyte count with a low percentage of lymphocytes and elevated ADA levels in the pleural effusion.…”
Section: Discussionmentioning
confidence: 99%